Transformational Leadership in Developing Work Culture: A Case Study at SD Negeri Danurejo, Kedu District, Temanggung Regency - Kurnia Margi Ariyanti; Sri Wahyuningsih; Santika Kurnianingrum; Nurkolis Nurkolis (FKIP - Universitas Riau, 2026)
Educational leadership plays an important role in improving school quality through the development of a positive and professional work culture. This study aimed to analyze the transformational leadership of the principal in developing work culture at SD Negeri Danurejo, Kedu District, Temanggung Regency. This study employed a qualitative case study design. The research subjects consisted of the principal, teachers, educational staff, and school committee selected through purposive sampling. Data were collected through interviews, observations, and documentation. Data validity was examined using source and technique triangulation, while data analysis employed the interactive model of Miles, Huberman, and Saldaña. The findings revealed that the principal implemented transformational leadership through building a shared vision, exemplary behavior, open communication, and teacher involvement in decision-making. The strategies included fostering work discipline, strengthening collaboration, enhancing teacher competence, and providing appreciation for teacher performance. Transformational leadership positively influenced the school work culture, as reflected in improved discipline, work motivation, collaboration, and teacher professionalism. These findings imply that principals should strengthen participatory leadership, effective communication, and continuous professional support to sustain a positive work culture. Educational administrators may also use these findings to design leadership development programs that support school effectiveness and organizational performance.